Hospitalization costs and out-of-pocket (OOP) payment in lung cancer patients in Iran: Health Sector Evolution Plan (HSEP) has reduced OOP payments and improved financial protection. - Habib Jalilian; Somayeh Heydari; Elnaz Javanshir; Khosro Jamebozorgi; Nazanin Mir; Abbas Eshraghi; Saeedeh Fehresti (PLoS ONE)
Background and objective In Iran, Health Sector Evolution Plan, the most significant reform in the healthcare system in recent decades, has been launched since 2014 with the objective of achieving universal health coverage, decreasing out-of-pocket health expenditures and improving access to health services in hospitals and clinics affiliated to the Ministry of Health and Medical Education (MOHME). This study aimed to estimate the hospitalization costs of lung cancer and the impact of HSEP on hospitalization costs of lung cancer and patients' contribution in Iran between 2010 and 2017. Methods This was a prevalence-based cost of illness study with a bottom-up costing approach. The sample size included 1778 lung cancer patients hospitalized in the Imam Reza hospital in Tabriz, Iran, between May 5, 2010, to May 5, 2014, and four years after the implementation of Health Sector Evolution Plan: from May 5, 2014, to May 5, 2017. The analysis was conducted from a societal perspective. Data were extracted from the electronic medical records of patients and were analyzed using SPSS V22.0, STATA V13.0 and Microsoft Excel 2016. The Interrupted Time-Series design was applied to estimate the impact of the implementation of HSEP on hospitalization costs and patient contribution rate for reimbursement of costs. Results The mean hospitalization costs of lung cancer before and after the implementation of Health Sector Evolution Plan was estimated at 2860 ± 4575 and 5300 ± 8880 PPP (Current International $), respectively. Moreover, the amount of out-of-pocket payments reduced from 705 PPP (Current International$) (22.16%) before the implementation of Health Sector Evolution Plan to 480 PPP (Current International $) (10.5%) after its implementation. the hospitalization costs went up moderately before the HSEP (increased from 2320 $ in 2010 to 3025 $ in 2013). After the HSEP, it continued to rise, but with a more significant increase until 2016. Then, in 2016, it reached a peak (6395 $) before dropping in 2017 (5005 $). Regarding patient contribution, before the HSEP, the percentage of patient contributions increased from 19.45 in 2010 to 24.28 in 2013. With HSEP's implementation, this fell dramatically to 14.47 and continued to decline, reaching 7.99% in 2016. In 2017, patient contribution increased again and reached 9.58%. Conclusion Overall, hospitalization costs experienced an upward trend over the course of study, but this trend considerably intensified further after the HSEP. The patient contribution demonstrated an upward trend before HSEP, followed by a significant decline post-HESP, and the percentage of out-of-pocket payments reduced after implementation of HSEP. Therefor this plan has been successful in achieving the goal of financial protection of patients.